1999
DOI: 10.1007/s004420050900
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific and intraspecific variation in tree seedling survival: effects of allocation to roots versus carbohydrate reserves

Abstract: We examined interspecific and intraspecific variation in tree seedling survival as a function of allocation to carbohydrate reserves and structural root biomass. We predicted that allocation to carbohydrate reserves would vary as a function of the phenology of shoot growth, because of a hypothesized tradeoff between aboveground growth and carbohydrate storage. Intraspecific variation in levels of carbohydrate reserves was induced through experimental defoliation of naturally occurring, 2-year-old seedlings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
231
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(263 citation statements)
references
References 42 publications
23
231
0
9
Order By: Relevance
“…These results agree with those published by other authors (Reich et al 1998;Huante et al 1992;Paz 2003), although this study was carried out on a broader plant size gradient and on roots larger than 2 mm. The thicker root system of non-pioneer species supports the hypothesis that allocation to storage or defence is favoured in these species at the expense of soil exploration (Kobe 1997;Canham et al 1999). Investment in soil exploration would in contrast be needed by pioneer species to compensate higher aboveground development (i.e.…”
Section: Variation In Root Allocation and Architecturementioning
confidence: 55%
“…These results agree with those published by other authors (Reich et al 1998;Huante et al 1992;Paz 2003), although this study was carried out on a broader plant size gradient and on roots larger than 2 mm. The thicker root system of non-pioneer species supports the hypothesis that allocation to storage or defence is favoured in these species at the expense of soil exploration (Kobe 1997;Canham et al 1999). Investment in soil exploration would in contrast be needed by pioneer species to compensate higher aboveground development (i.e.…”
Section: Variation In Root Allocation and Architecturementioning
confidence: 55%
“…As a consequence, the root biomass was underestimated in this study. Root samples were ground using a mechanical mill, after which, approximately 0.1 g ground aliquots were analyzed for total non-structural carbohydrate (TNC) through the conversion of sugars and starches to glucose equivalents followed by colorimetric analysis (Canham et al, 1999). …”
Section: Non-structural Carbohydratementioning
confidence: 99%
“…2). The fact that preferential carbon allocation to storage in late-successional species is more characteristic of tropical than of temperate forests (Kitajima 1994, Canham et al 1999, Lusk and Piper 2007, Myers and Kitajima 2007, Poorter and Kitajima 2007, Piper 2015 is therefore unlikely to be explained by differential herbivore responses to light availability gradients in tropical versus temperate forests. Although the low opportunity cost of allocation to storage in shaded understories has been emphasized (Kobe 1997), it is unclear why similar patterns have not consistently been observed in shade-tolerant species of temperate forests (Canham et al 1999, Lusk andPiper 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have found evidence linking seedling shade tolerance to carbon allocation to storage (Canham et al 1999, Kitajima 1994, Poorter and Kitajima 2007, several others did not (Canham et al 1999, Lusk and Piper 2007, Piper 2015, Piper et al 2009, 2017. One possible explanation for the discrepancy is that, in some regions, the levels of understorey herbivory are insufficient to select for herbivory tolerance.…”
Section: Introductionmentioning
confidence: 99%